Genetic linkage map of a high yielding FELDA Deli×Yangambi oil palm cross - Seng, Tzer Ying; Mohamed Saad, Siti Hawa; Chin, Cheuk Weng; Ting, Ngoot Chin; Harminder Singh, Rajinder Singh; Qamaruz Zaman, Faridah; Tan, Soon Guan; Syed Alwee, Sharifah Shahrul Rabiah (Public Library of Science, 2011)
Enroute to mapping QTLs for yield components in oil palm, we constructed the linkage map of a FELDA high yielding oil palm (Elaeis guineensis), hybrid cross. The parents of the mapping population are a Deli dura and a pisifera of Yangambi origin. The cross out-yielded the average by 8–21% in four trials all of which yielded comparably to the best current commercial planting materials. The higher yield derived from a higher fruit oil content. SSR markers in the public domain - from CIRAD and MPOB, as well as some developed in FELDA - were used for the mapping, augmented by locally-designed AFLP markers. The female parent linkage map comprised 317 marker loci and the male parent map 331 loci, both in 16 linkage groups each. The number of markers per group ranged from 8–47 in the former and 12–40 in the latter. The integrated map was 2,247.5 cM long and included 479 markers and 168 anchor points. The number of markers per linkage group was 15–57, the average being 29, and the average map density 4.7 cM. The linkage groups ranged in length from 77.5 cM to 223.7 cM, with an average of 137 cM. The map is currently being validated against a closely related population and also being expanded to include yield related QTLs.